Medeniyet âleminde yazı ve İslâm medeniyetinde kalem güzeli - Yazır, Mahmud Bedreddin, 1893-1952. (Ankara Ankara)
2 c. (1. c. xvi, 160, [1] s., [9] y. resim (renkli) ; 2. c. xv s., s. [161]-291, [16] y. resim (renkli))